CHILDREN’S SINGING: REFLECTIONS ON A VOCAL TEACHING IN LITHUANIA AND TAIWAN - Rauduvaite, Asta; Lasauskiene, Jolanta; Abramauskiene, Jolanta; Chuang, Ming (PEOPLE: International Journal of Social Sciences, 2017)
The research is concerned with the aim of comparing children’s singing and vocal teaching development in Lithuania and Taiwan. Singing is the most noticeable feature of musical culture of the nation. Seeking the continuity of traditions of teaching singing, the nurturance of children’s singing in various countries is considered to be one of the key objectives of music education. Therefore, the research teams from Lithuania and Taiwan have decided that the importance of the development of a child’s voice requires more attention. In total 150 6-8 yearold children took part in the research (testing): 75 children in each age group were tested in Lithuania and Taiwan. The methodology for “Children’s Singing Voice Measure” (CSVM) was used in the research. The conducted research highlighted the tendencies of expression of 6-8 year-old children’s singing voice skills in musical education classes in Lithuania and Taiwan. It was revealed that the ability of 6-8 year-old children to control the singing voice range is developed insufficiently. The article was written implementing the international tripartite research project “Coordination between Musical Hearing and Vocal Apparatus of 6-8 Year-Old Children during the Process of Singing: Comparative Study in Latvia, Lithuania and Taiwan” (TAP-LLT-14-016).